Cortisol and hypothalamic–pituitary–gonadal axis hormones in follicular-phase women with fibromyalgia and chronic fatigue syndrome and effect of depressive symptoms on these hormones - Gur, Ali; Cevik, Remzi; Nas, Kemal; Colpan, Leyla; Sarac, Serdar (Arthritis research & therapy, 2004)
We investigated abnormalities of the hypothalamic-pituitary-gonadal axis and cortisol concentrations in women with fibromyalgia and chronic fatigue syndrome (CFS) who were in the follicular phase of their menstrual cycle, and whether their scores for depressive symptoms were related to levels of these hormones. A total of 176 subjects participated - 46 healthy volunteers, 68 patients with fibromyalgia, and 62 patients with CFS. We examined concentrations of follicle-stimulating hormone, luteinizing hormone (LH), estradiol, progesterone, prolactin, and cortisol. Depressive symptoms were assessed using the Beck Depression Inventory (BDI). Cortisol levels were significantly lower in patients with fibromyalgia or CFS than in healthy controls (P < 0.05); there were no significant differences in other hormone levels between the three groups. Fibromyalgia patients with high BDI scores had significantly lower cortisol levels than controls (P < 0.05), and so did CFS patients, regardless of their BDI scores (P < 0.05). Among patients without depressive symptoms, cortisol levels were lower in CFS than in fibromyalgia (P < 0.05). Our study suggests that in spite of low morning cortisol concentrations, the only abnormalities in hypothalamic-pituitary-gonadal axis hormones among follicular-phase women with fibromyalgia or CFS are those of LH levels in fibromyalgia patients with a low BDI score. Depression may lower cortisol and LH levels, or, alternatively, low morning cortisol may be a biological factor that contributes to depressive symptoms in fibromyalgia. These parameters therefore must be taken into account in future investigations.